Extracellular and Intracellular Angiotensin II Regulate the Automaticity of Developing Cardiomyocytes via Different Signaling Pathways - Qi, Zenghua; Wang, Tao; Chen, Xiangmao; Wong, Chun Kit; Ding, Qianqian; Sauer, Heinrich; Chen, Zhi-Feng; Long, Cheng; Yao, Xiaoqiang; Cai, Zongwei; Tsang, Suk Ying (Frontiers in Molecular Biosciences, 2021)
Angiotensin II (Ang II) plays a key role in regulating various physiological processes. However, little is known about the existence of intracellular Ang II (iAng II), whether iAng II would regulate automaticity of early differentiating cardiomyocytes, and the underlying mechanism involved. Here, iAng II was detected by immunocytochemistry and ultra-high performance liquid chromatography combined with electrospray ionization triple quadrupole tandem mass spectrometry in mouse embryonic stem cell-derived cardiomyocytes (mESC-CMs) and neonatal rat ventricular myocytes. Expression of AT1R-YFP in mESC-CMs revealed that Ang II type 1 receptors were located on the surface membrane while immunostaining of Ang II type 2 receptors (AT2R) revealed that AT2R were predominately located on the nucleus and the sarcoplasmic reticulum. While extracellular Ang II increased spontaneous action potentials (APs), dual patch clamping revealed that intracellular delivery of Ang II or AT2R activator C21 decreased spontaneous APs. Interestingly, iAng II was found to decrease caffeine-induced increase in spontaneous APs and caffeine-induced calcium release, suggesting that iAng II decreased spontaneous APs via AT2R- and ryanodine receptor-mediated pathway. This is the first study provides evidence of the presence and function of iAng II in regulating automaticity behavior of ESC-CMs and may therefore shed light on the role of iAng II in fate determination.